Parental Background, Parenting Practices, Sibling Birth Order and Children’s Theory of Mind - Nisa Praditya Ar Rizqi (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2025)
Parental background, parenting, and sibling birth order have been reported in many studies to be associated with children's Theory-of-Mind (ToM). However, these studies were not yet able to foresee the overall contribution of each factor related to children's social cognition, in this case, the theory of mind. This present study aimed to fill this gap by investigating which factors dominate the contribution to ToM: whether parent’s education, occupation, parental attitudes (parenting), or siblingship factors. The participants in this study were 225 preschool children (ages 4–6 years) and their parents living in the urban Jakarta Metropolitan Area. Children participants were tested using the 5-step ToM Scale in their respective pre-schools by their native speaker (Bahasa Indonesia). The parents were asked to report their demographic data, children's family background, and parenting assessed by the Parenting Attitudes Inventory. Both research instruments have been tested for its reliability and consistency after being translated to Bahasa Indonesia. The statistical analysis indicated that all independent variables (i.e., parents’ demographic background, parenting, and siblingship) 37,3% contributed on children theory-of-mind understanding. Mother education level is significant and the most affecting variable on children ToM. In contrast, while mother's occupation was negatively affecting children’s ToM, having a younger sibling(s) has a beneficial effect on understanding ToM. Finally, this study does not find any relationship between children’s ToM with numbers of family living in the house (family size), number of siblings, and children gender.